Oropouche virus as an emerging cause of acute febrile illness in Colombia. Issue 1 (31st December 2022) - Ciuoderis, Karl A.; Berg, Michael G.; Perez, Lester J.; Hadji, Abbas; Perez-Restrepo, Laura S.; Aristizabal, Leidi Carvajal; Forberg, Kenn; Yamaguchi, Julie; Cardona, Andres; Weiss, Sonja; Qiu, Xiaoxing; Hernandez-Ortiz, Juan Pablo; et al.
ABSTRACT: Arbovirus infections are frequent causes of acute febrile illness (AFI) in tropical countries. We conducted health facility-based AFI surveillance at four sites in Colombia (Cucuta, Cali, Villavicencio, Leticia) during 2019-2022. Demographic, clinical and risk factor data were collected from persons with AFI that consented to participate in the study ( n = 2, 967). Serologic specimens were obtained and tested for multiple pathogens by RT–PCR and rapid test (Antigen/IgM), with 20.7% identified as dengue positive from combined testing. Oropouche virus (OROV) was initially detected in serum by metagenomic next-generation sequencing (mNGS) and virus target capture in a patient from Cúcuta. Three additional infections from Leticia were confirmed by conventional PCR, sequenced, and isolated in tissue culture. Phylogenetic analysis determined there have been at least two independent OROV introductions into Colombia. To assess OROV spread, a RT-qPCR dual-target assay was developed which identified 87/791 (10.9%) viremic cases in AFI specimens from Cali (3/53), Cucuta (3/19), Villavicencio (38/566), and Leticia (43/153). In parallel, an automated anti-nucleocapsid antibody assay detected IgM in 27/503 (5.4%) and IgG in 92/568 (16.2%) patients screened, for which 24/68 (35.3%) of PCR positives had antibodies. Dengue was found primarily in people aged <18 years and linked to several clinical manifestations (weakness, skin rash and petechiae), whereas Oropouche cases were associated with the location, climate phase, and odynophagia symptom. Our results confirm OROV as an emerging pathogen and recommend increased surveillance to determine its burden as a cause of AFI in Colombia. GRAPHICAL ABSTRACT: UF0001